Informational needs of gastrointestinal oncology patients. (7th November 2014) - Papadakos, Janet; Urowitz, Sara; Olmstead, Craig; Jusko Friedman, Audrey; Zhu, Jason; Catton, Pamela
Abstract: Objectives: In response to the dearth of consumer health information for patients with gastrointestinal cancers, this study examined the informational needs of these patients to build a plan for future resource development. Although studies have examined informational needs of some such cancers, no published literature has investigated the comprehensive informational needs across all sites of gastrointestinal cancer. Methods: A cross‐sectional needs assessment comprising a self‐administered questionnaire was conducted at an ambulatory gastrointestinal oncology clinic in Toronto, Canada. Patient informational needs were measured, including importance of information, amount desired and preferred mode of delivery. Informational needs were grouped into six domains: medical, practical, physical, emotional, social and spiritual. Results: Eighty‐two surveys were analysed. The majority of the respondents were male (53.8%), over the age of 50 (77.8%), and born outside of Canada (51.9%). While many did not speak English as a child (46.3%), and do not speak English at home (22.2%), nearly all indicated comfort with receiving health information in English (97.5%). The majority of respondents were college educated (79.3%) and married (73%). Multiple cancer types were reported; the most common being colorectal (39%), followed by pancreatic (12%) and cancers of the gallbladder or bile duct (12%). Overall, respondents placed highest importance on medical information ( P < 0.001). Preferred education modalities were pamphlets, websites and one‐on‐one discussions with health‐care professionals. Conclusions: This study highlights the principal informational needs of patients with gastrointestinal malignancies, along with preferred modality for information delivery. This information will guide the development of educational resources for future patients.